DAYA PIKAT PERSUASIF PEDAGANG IKAN DI PASAR SARONGGI KABUPATEN SUMENEP MADURA - Suhartatik Suhartatik (RETORIKA: Jurnal Ilmu Bahasa, 2017)
Abstract Traders should know much the ways how to communncate with the buyers or consumers. It means that the buyers or the consumers will take an interest with what they are selling. They, of course, have their own ways to promote theirs so that the buyers or consumers will buy their goods. Using good speech acts and convinced words are the ways that they must have to convince the buyers or consumers to buy. This research is a descriptive. It is focused on how speech act and persuasive power done by fish traders will influence the buyers or consumers at Saronggi Market of Sumenep regency-Madura. The approach used is pragmatic – the approach bases on the friends’, reactions and ideas. The method used is the monitoring of involving statements – the buyers or consumers also hold a dialogue with the traders.The result of the research shows that there are speech acts such as: lecutionary, illecitionary, and perlocutionary acts done by the fish traders at at Saronggi Market of Sumenep regency-Madura. And in addition to that from those speech acts also show the existing of persuasive communication done by the fish traders to the buyers or consomers either from the phrase, clause and sentence levels.Many traders use the phrase level in order to save their speech act but it has strong sense to attract the buyers to be. Meanwhile the clause and sentence levels a re used by them to greet the buyers or consumers, they are among others: Ebhu (mother), Mbhuk (older sister), Le’ (younger sister), Bhing (the vacation of a girl), Jhi (hajj). In the sentence level the traders also use oral, informative, connotation, imperative and interrogative sentence Keywords: Persuasive Attractive Power, Fish traders